Fulfillment of Clean Water Needs for Households in Waeeken Village, South Buru Regency - Teslatu, Tineke; Salakory, Melianus; Leuwol, Ferdinad Salomo (Jurnal Pendidikan Geografi Unpatti, 2023)
Waeeken Village in South Buru Regency faces challenges in meeting clean water needs. Although groundwater sources are a priority due to their superior quality and lower pollution impacts, accessibility, and geographical limitations are obstacles. In the dry season, people depend on clean water from rock sources, although they are difficult to reach. Research findings show that there is a high water need per family, that it exceeds 120 liters per day, and that there is a dependence on water sources with limitations. Although there are efforts to use rainwater, difficulties remain due to the distance that must be traveled. The study "Clean Water Needs and Fulfillment in Households in Waeeken Village" reflects an awareness of the complexity of water needs and the challenges of its availability to understand these dynamics in the geographical context and needs of the local community. The study was conducted in Waeeken Village, South Buru Regency. The type of research is descriptive and auditive research, which aims to describe or depict the facts of clean water, the availability of clean water, and the fulfillment of clean water or conditions or symptoms that appear in Waieeken Village, Fena-Fafan District, South Buru Regency. The research variables are Clean Water Needs and Fulfillment for Households, which are the indicators of clean water sources, clean water needs, and fulfillment. The availability of clean water to meet family needs in Waeeken Village, South Buru Regency, based on study findings and analysis, can be characterized as follows: This condition occurs due to the lack of rainfall and adequate air protection infrastructure, which causes the current supply of pure water to be below the desired standard. The impact of this situation is very significant for community welfare, primarily related to the availability of clean water for household needs and the need for clean water per liter per day in Waeeken Village, South Buru Regency.